Pemanfaatan Daun Sirih Hijau (Piper Betle L.) Sebagai Bahan Baku Pembuatan Oleoresin Dengan Menggunakan Metode Ekstraksi - Ultalalah Audadi; Ratni Dewi; Zuhra Amalia (Politeknik Negeri Lhokseumawe, 2025)
Green betel leaf (Piper betle L.) is a herbal plant that has long been known in Indonesia because it has many medical benefits and other uses in various traditional ceremonies. Ingredients in betel leaves such as essential oils (cavicol, eugenol), flavonoids, and tannins can function as antimicrobials, antifungals, and antioxidants. Betel leaves are very easy to decline in quality so they need to be processed further. One of the efforts to maintain the quality and increase the use value of betel leaves is by processing them into oleoresin. Oleoresin functions as a raw material for adding flavor, aroma, natural preservatives and others. The purpose of this study was to determine the best raw material size, time, and extraction temperature for the oleoresin produced. The process method uses sokletation extraction and then a rotary vacuum evaporator is used to remove the remaining ethanol solvent in the solvent. The solvent used was 70% ethanol with a material and solvent ratio of 1:10 and three factors: raw material size of 9 mesh (2 mm) and 20 mesh (250 Î¼m), time of 120, 135, 150, 165, and 180 minutes, and temperature of 75 and 80oC. Oleoresin obtained was tested including water content, yield, specific gravity, organoleptic (color, aroma, shape), and GC-MS (Gas Chromatography-Mass Spectrometry). Based on the research, the best results were obtained from the value of raw material moisture content of 7.74%, yield of 30%, specific gravity of 1.0196 g/mL, and oleoresin content of 5.10% resulting in greenish brown oleoresin extract in liquid form and has a distinctive aroma of betel leaf.